1989
DOI: 10.1097/00004032-198908000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and Chemical Modification of Tc by Soil Bacteria

Abstract: Bioaccumulation and chemical modification of pertechnetate (TcO4-) by aerobically and anaerobically grown soil bacteria and by pure cultures of sulfate-reducing bacteria (Desulfovibrio sp.) were studied to gain insight on the possible mechanisms by which bacteria can affect the solubility of Tc in soil. Aerobically grown bacteria had no apparent effect on TcO4-; they did not accumulate Tc nor modify its chemical form. Anaerobically grown bacteria exhibited high bioaccumulation and reduced TcO4-, enabling its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 6 publications
0
29
0
1
Order By: Relevance
“…Yet to correlate this result to a direct or an indirect effect of the microbial activity of the soil was difficult. Contrary to Se, microbially-mediated reduction of Tc(VII) was proved only in anaerobic condition [7,8]. But abiotic reduction of Tc(VII) should not be excluded [4].…”
Section: Batch Experimentsmentioning
confidence: 94%
See 1 more Smart Citation
“…Yet to correlate this result to a direct or an indirect effect of the microbial activity of the soil was difficult. Contrary to Se, microbially-mediated reduction of Tc(VII) was proved only in anaerobic condition [7,8]. But abiotic reduction of Tc(VII) should not be excluded [4].…”
Section: Batch Experimentsmentioning
confidence: 94%
“…These reduction reactions can be achieved abiotically by heterogeneous reactions with FeII-containing minerals for example [3,4]. But they have also been proved to be microbially mediated, resulting either from direct interaction between Se / Tc and some microorganisms [5,6,7,8] or from physico-chemical changes due to the microbial activity [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Complexation of TcO Ϫ 4 with humic acid and other dissolved organic carbon is only possible when the Eh-value becomes negative (E 0 =Ϫ0.50 V for Tc(VII)/Tc(IV)), (Rößler et al, 2000). As noted by Lieser and Bauscher (1987) (Henrot, 1989). Literature reports therefore suggest that neither chemical nor biological factors have much impact on the generally high availability of 99 Tc in aerobic soils.…”
Section: Tc In Aerobic and Anaerobic Soilsmentioning
confidence: 95%
“…It seems likely that they might also play a role in progressive immobilization of 99 Tc. A number of authors have previously suggested that anaerobic microsites in soils might be important in TcO Ϫ 4 reduction (Hoffman et al, 1982;Henrot, 1989;Echevaria et al, 1997) but the potential scale of the process may only now be emerging with recent research into denitrification.…”
Section: Tc and Soils Of The Worldmentioning
confidence: 99%
“…La sorption du technétium est corrélée principalement aux teneurs en carbone organique, en oxydes de fer et d'aluminium et en argile des sols (Gu et Schulz, 1991). Les formes réduites du technétium forment des complexes très stables avec la matière organique, en particulier avec les acides humiques (Sekine et al, 1997 ;Henrot, 1989 ;Stalmans et al, 1996). Le technétium est ainsi majoritairement présent dans les horizons organiques du sol.…”
Section: Technétiumunclassified